Enhancing Management Transparency in the Distribution of Direct Cash Assistance (BLT) in Anabanua Village: A Study on Document Accessibility, Information Clarity, and Regulatory Compliance. - Syamsiah (Meraja journal, 2025)
[Full Paper] to pdf Copyright (c) 2025 Meraja journal